2016
DOI: 10.1002/pro.3054
|View full text |Cite
|
Sign up to set email alerts
|

While the revolution will not be crystallized, biochemistry reigns supreme

Abstract: Single-particle cryo-electron microscopy (EM) is currently gaining attention for the ability to calculate structures that reach sub-5 Å resolutions; however, the technique is more than just an alternative approach to X-ray crystallography. Molecular machines work via dynamic conformational changes, making structural flexibility the hallmark of function. While the dynamic regions in molecules are essential, they are also the most challenging to structurally characterize. Single-particle EM has the distinct adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 126 publications
(258 reference statements)
0
28
0
Order By: Relevance
“…3D, E, F, Movie 2), in contrast to earlier studies where the tail could not be identified [1] or was not analyzed in 3D [9]. These earlier studies illustrate the difficulties of visualizing the myosin tail by cryo-EM and the ease with which it can be seen by negative staining, our technique of choice (see [33, 34] and Methods). While the resolution of the reconstruction is not high (due partly to flexibility of the molecule), we could easily detect the different domains of the myosin heavy chain and light chains, revealing steric blocking of specific regions of the heads by the tail that explains how the molecule is so effectively switched off in the quiescent state [31].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…3D, E, F, Movie 2), in contrast to earlier studies where the tail could not be identified [1] or was not analyzed in 3D [9]. These earlier studies illustrate the difficulties of visualizing the myosin tail by cryo-EM and the ease with which it can be seen by negative staining, our technique of choice (see [33, 34] and Methods). While the resolution of the reconstruction is not high (due partly to flexibility of the molecule), we could easily detect the different domains of the myosin heavy chain and light chains, revealing steric blocking of specific regions of the heads by the tail that explains how the molecule is so effectively switched off in the quiescent state [31].…”
Section: Discussionmentioning
confidence: 63%
“…Turkey gizzard smooth muscle myosin at physiological ionic strength (0.15 M NaAc) in the presence of ATP was observed by negative staining with 1% uranyl acetate, a technique providing key insights into protein domain structures and interactions [33, 34]. The compact, folded (10S) conformation dominated the EM images, with a small number of antiparallel 10S dimers, displaying a dumbbell-shaped structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, during the process of specimen preparation, where a thin aqueous suspension is created and plunge-frozen, functionally relevant protein complexes that are stable in bulk solution may become dissociated [15-17]. In addition, proteins and protein complexes in aqueous solution are intrinsically flexible to varying extents [18], creating structural heterogeneity that can be even more pronounced in multi-domain proteins and multi-protein complexes [19,20].…”
Section: Introductionmentioning
confidence: 99%